The localisation of ED1 antibody in the resorbing hard tissues of the periodontium - Dreyer C.W; Pierce A.M (Sciendo, 2001)
A dental hard tissue resorptive model was used to determine the periodontal ligament (PDL) distribution of lysosomal membrane antibody ED1 to cells of the macrophage-phagocyte lineage. Immunolabel was identified in mononuclear cells around inflammatory sites in the PDL, while multinu-clear cells were labelled in resorption bays present in both bone and dentine. As repair of the tissues occurred, the label became less obvious. The presence of strong ED1 label in alveolar bone marrow provided evidence supporting the haemopoietic origin of the similarly labelled PDL cells. Also, evidence confirming the current theory that multinucleated resorptive cells differentiate along a monocyte-macrophage pathway was provided. It was concluded that ED1 is a positive PDL marker for mononuclear and multinuclear cells involved in the inflammatory and resorptive processes.